2022
DOI: 10.1371/journal.pone.0274598
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from focal segmental glomerulosclerosis pediatric patients induce STAT3 activation and mesangial cell proliferation

Abstract: Introduction Primary focal segmental glomerulosclerosis (FSGS), a major cause of end-stage kidney disease (ESKD) in adolescents and young adults, is attributable to recognized genetic mutations in a minority of cases. For the majority with idiopathic primary FSGS, the cause of the disease is unknown. We hypothesize that extracellular vesicle (EVs), that carry information between podocytes and mesangial cells, may play a key role in disease progression. Material & methods A total of 30 participants (20 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…They are more than just waste-exporting vesicles, as they enable the transfer of mRNAs, microRNAs, DNA, and proteins across cells [ 22 ]. EVs have been shown to allow for intercellular communication within the nephron [ 23 ] and play a role in signal transduction [ 24 , 25 , 26 , 27 ]. EVs are a rich source of biomarkers, and recent research has shown that they may play a role in the pathophysiology of hypertension [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are more than just waste-exporting vesicles, as they enable the transfer of mRNAs, microRNAs, DNA, and proteins across cells [ 22 ]. EVs have been shown to allow for intercellular communication within the nephron [ 23 ] and play a role in signal transduction [ 24 , 25 , 26 , 27 ]. EVs are a rich source of biomarkers, and recent research has shown that they may play a role in the pathophysiology of hypertension [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…EVs from the FSGS group activated the signal transducer and activator of the transcription 3 (STAT3) pathway, which presumably leads to a dose-dependent increase in mesangial cell proliferation. When mesangial cells were challenged with EVs isolated from FSGS patients, proliferating cell nuclear antigen (PCNA), Ki67, and cell proliferation were also significantly increased [10].…”
Section: Focal Segmental Glomerulosclerosismentioning
confidence: 99%
“…The specific composition and function of EVs, which contain a subset of common proteins involved in biogenesis and trafficking, as well as a signature from the cell or tissue of origin, are explained by their different subcellular origin [6,9]. Because EV release and uptake are both dynamic processes regulated by a variety of mechanisms, it is difficult to accurately estimate the duration and concentration of EVs that a specific cell type would be exposed to in a physiological or pathophysiological scenario [10]. EVs modulate leukocyte adhesion, differentiation, and vascular function in inflammation, according to mechanistic data, and these studies have greatly improved our understanding of these pathophysiologic processes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, Eroglu et al (2021) have found that patients with SSNS during relapse had higher protein content in circulating plasma EVs, especially proteins that involved actin cytoskeleton rearrangement, such as Rasrelated C3 botulinum toxin substrate 1 (RAC-1) [242]. EVs have also been shown to induce mesangial cell proliferation in pediatric patients with FSGS through the phospho-STAT-3 pathway [243]. This topic has been recently reviewed elsewhere [244].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%